Strategi Komisi Pemilihan Umum Dalam Meningkatkan Partisipasi Politik Pemilih Pemula Pada Pemilihan Bupati dan Wakil Bupati 2018 di Kabupaten Pinrang - Lestari, Dewi Sri; Azikin, Ruskin; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2020)
This study purposed to describe how the the general election commission strategy in increasing the political participation of novice voters in the election of Regent and Vice of Regent in Pinrang Regency, 2018. This study used the Salusu theory. The method was descriptive qualitative research. The results of this study showed that the strategy used to increase the political participation of novice voters in the election commission in collaboration with democratic volunteers and several other community organizations in conducting socialization activities to improve performance even though it was not done routinely, socialization was three segment of society including high school student, student and the general public in accordance with the methods used, as well as utilizing electronic media and internet media. The determinant factor why novice voters did not participate in voting were daily activities, the influence of the family environment, and feelings of inadequacy.